The Oxford Handbook of the History of Consumption 2012
DOI: 10.1093/oxfordhb/9780199561216.013.0024
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Subversions: Modern Colonialism, Globalization, and Commodity Culture

Abstract: Scholars studying the history of modern colonialism have been more reluctant to make strongly contrarian claims about consumerism and commodification similar to those made by early modern Europeanists because they are more unsettled by some of the implications of their own studies. Modern consumer culture is strongly mapped to ‘Westernization’ and globalization. There is a very large class of scholarly studies that in some respect or another discuss the association between colonialism and consumption in ninete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In historical studies, this framework is demonstrated through Mintz’s (1986) seminal scholarship on sugar, which shows how the commodity’s biography changed as it passed from producer to consumer across geographies and societies. By studying how the “commodities themselves also shape consumption practices through their concrete materiality and in terms of the embedded histories of meanings associate with them” (Burke, 2012, p. 478), it engages historians to rethink commodities produced in colonies as more complex than mere tools of imperialistic projects.…”
Section: Colonialism and The Consumer Culture Of Tinmentioning
confidence: 99%
“…In historical studies, this framework is demonstrated through Mintz’s (1986) seminal scholarship on sugar, which shows how the commodity’s biography changed as it passed from producer to consumer across geographies and societies. By studying how the “commodities themselves also shape consumption practices through their concrete materiality and in terms of the embedded histories of meanings associate with them” (Burke, 2012, p. 478), it engages historians to rethink commodities produced in colonies as more complex than mere tools of imperialistic projects.…”
Section: Colonialism and The Consumer Culture Of Tinmentioning
confidence: 99%
“… 2. Unlike Mayer, I am not comfortable with applying the term ‘middle class’ to pre-modern societies, and, furthermore, I am wary of implying such a modern social and economic concept by speaking of ‘middling’ classes, as this modern model of class structure is a distinct product of modernity and industrialization, expanding into a global middle class (see López and Weinstein 2012; Burke 2012). It would be anachronistic to impose such a class structure onto the Roman world.…”
mentioning
confidence: 99%